Plight of the Rohingya : ASEAN credibility again at stake - Yang Razali Kassim (2013)
The suffering of the Rohingya in Myanmar's Rakhine state is putting pressure on ASEAN to intervene. Coming just before their 21st Summit, the wisdom and stewardship of ASEAN leaders will be tested once again.